EMPOWERMENT OF GRINTING VILLAGE HOUSEWIVES DURING COVID-19 THROUGH KANGKUNG VEGETABLE CULTIVATION TRAINING ACTIVITIES - Nur Hanna, Nur; Fatih, Widya Dwi Nur Alma; Febriani Nursyafitri, Febriani; Mazidatul Inayah, Mazidatul; Wening, Pertiwi Mega (Universitas Negeri Semarang, 2020)
Organic vegetables are one of the sources of nutrients needed by humans. There is some nutritional content in vegetables that are not found in other food sources. Vegetables contain a lot of fiber that has many roles in the digestive process. One of them is Kale cultivation, planting Kale using soil media and polybag is one form of innovation that can be done to increase the knowledge of Grinting village people about planting vegetables more simply while also to improve the skills of the community in the midst of the Covid-19 pandemic. Planting kale using soil media and polybags only requires narrow land so it is more economically efficient because it does not require much complicated maintenance. Kale cultivation training using soil media and polybags targets housewives who aim to improve knowledge of balanced nutritional fulfillment for families during the Covid-19 pandemic. Sayur organik merupakan salah satu sumber nutrisi yang dibutuhkan oleh manusia. Ada beberapa kandungan gizi pada sayur yang tidak terdapat pada sumber bahan makanan lain. Sayur mengandung banyak serat yang memiliki banyak peranan dalam proses pencernaan. Salah satunya budidaya kangkung, penanaman kangkung menggunakan media tanah dan polybag merupakan salah satu bentuk inovasi yang dapat dilakukan untuk menambah pengetahuan masyarakat Desa Grinting mengenai penanaman sayuran yang lebih simpel sekaligus untuk meningkatkan keterampilan masyarakat di tengah masa pandemi Covid-19. Penanaman kangkung menggunakan media tanah dan polybag hanya membutuhkan lahan sempit sehingga lebih efisien secara ekonomi karena tidak terlalu membutuhkan perawatan yang rumit. Pelatihan budidaya kangkung dengan menggunakan media tanah dan polybag menyasar ibu rumah tangga yang bertujuan untuk meningkatkan pengetahuan pemenuhan gizi seimbang untuk keluarga selama masa pandemi Covid-19.